CHANGES IN VISUAL ACUITY IN PATIENTS WITH WET AGE-RELATED MACULAR DEGENERATION TREATED WITH INTRAVITREAL RANIBIZUMAB IN DAILY CLINICAL PRACTICE: The TWIN Study. Issue 9 (September 2015) - Souied, Eric H.; Oubraham, Hassiba; Mimoun, Gérard; Cohen, Salomon Y.; Quere, Stéphane; Derveloy, Audrey
Abstract : Purpose: The real-life LUMIERE study on patients with wet age-related macular degeneration treated with intravitreal ranibizumab in 2006 to 2009 showed that failure to follow recommendations was associated with lower efficacy than had been observed in the development phase. The TWIN Study reviewed the situation in 2010 to 2011. Methods: Retrospective, descriptive purely observational study of data acquired after 12 months of treatment with intravitreal ranibizumab. Results: In 881 patients (68% women, mean age, 79 years) treated by 21 ophthalmologists, the mean gain in visual acuity was +4.3 ± 15.4 letters (up from 3.2 ± 14.8 in 2006–2009; NS). Significant improvements were documented in the mean interval between diagnosis and treatment initiation (down from 12.6 ± 26.4–7.7 ± 10.9 days; P < 0.001), and in the percentage of patients who received a full course of induction treatment (56.6 vs. 39.6%; P < 0.001). After induction, hardly any patients were monitored every month as recommended, although retreatment was more assiduous (5.6 ± 2.3 vs. 5.1 ± 2.1 injections; P < 0.001). Conclusion: Despite improvements in key parameters, the effectiveness of intravitreal ranibizumab is still compromised by poor compliance with the guidelines, especially the frequency of postinduction monitoring that is now the most important determinant of successful treatment. Abstract : Ranibizumab in daily clinical practice.